2020
DOI: 10.1111/bjop.12449
|View full text |Cite
|
Sign up to set email alerts
|

Schema and deviation effects in remembering repeated unfamiliar stories

Abstract: In today's globalized world, we frequently encounter unfamiliar events that we may have difficulty comprehending – and in turn remembering – due to a lack of appropriate schemata. This research investigated schema effects in a situation where participants established a complex new schema for an unfamiliar type of story through exposure to four variations. We found that immediate recall increased across subsequent stories and that distortions occurred less frequently – participants built on the emerging schema … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 57 publications
(116 reference statements)
2
15
1
Order By: Relevance
“…free recall format), yet recall did not further benefit from the presence of deviations. The current results are inconsistent with previous research, which shows that the presence of deviations facilitates recall for all the witnessed events and for the targeted instance itself (Connolly et al, 2016;MacLean et al, 2018; although see Rubínová et al, 2021). Also, witnessing an instance that deviated from the script did not facilitate source monitoring as participants reported a similar number of internal intrusions in both deviation conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…free recall format), yet recall did not further benefit from the presence of deviations. The current results are inconsistent with previous research, which shows that the presence of deviations facilitates recall for all the witnessed events and for the targeted instance itself (Connolly et al, 2016;MacLean et al, 2018; although see Rubínová et al, 2021). Also, witnessing an instance that deviated from the script did not facilitate source monitoring as participants reported a similar number of internal intrusions in both deviation conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…In Study 1, our aim was to create stimuli that would resemble reallife repeated events in order to increase external validity relative to other laboratory-based repeated event studies (e.g., MacLean et al, 2018;Rubínová et al, 2020Rubínová et al, , 2021. Inspired by developmental repeated-event studies where children are typically interviewed about instances in which they directly participated (e.g., play sessions; Farrar & Boyer-Pennington, 1999), we created a series of marketing-themed visits that would be engaging for our target sample of adults.…”
Section: Study 1 Methodsmentioning
confidence: 99%
“…In brief, participants showed a gradual increase of accuracy of recall as the examples of stories go, which demonstrated that there was a build-up schema formation of the unfamiliar stories and helped us consolidate our memory formation as well. Besides, there were few memory errors of deviation from the original story shown than when it was tested with familiar stories [2]. In this case, it suggested that the build-up of new schema took over more of the attention when remembering events.…”
mentioning
confidence: 85%
“…In addition, schematic knowledge is not something that we are born inert. Rather, it is a build-up information that we developed and establish through our experiences in life, and thus sometimes it may change and deviates as time goes [2].…”
mentioning
confidence: 99%